2021
DOI: 10.18502/fem.v5i4.6692
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Clinical Characteristics and Laboratory Findings of COVID-19 between Intensive Care Unit and Non-Intensive Care Unit Pediatric Patients: A Multicenter, Retrospective, Observational Study from Iranian Network for Research in Viral

Abstract: Introduction: To date, little is known about the clinical features of pediatric COVID-19 patients admitted to intensive care units (ICUs). Objective: Herein, we aimed to describe the differences in demographic characteristics, laboratory findings, clinical presentations, and outcomes of Iranian pediatric COVID-19 patients admitted to ICU versus those in non-ICU settings. Methods: This multicenter investigation involved 15 general and pediatrics hospitals and included cases with confirmed severe acu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It was found that the most common symptoms reported in children, i.e., <18 years old, are cough and dyspnea ( Rabizadeh et al, 2020 ; Fahimzad et al, 2021 ) and fever and cough ( Hosseninasab et al, 2020 ; Mahmoudi et al, 2020 ; Armin et al, 2021 ; Hoseinyazdi et al, 2021 ; Mamishi et al, 2021 ; Soleimani et al, 2021 ; Keshavarz Valian et al, 2022 ). Gastrointestinal symptoms including vomiting, nausea, and diarrhea were reported but to a lesser extent ( Hosseninasab et al, 2020 ; Mamishi et al, 2020 ; Armin et al, 2021 ; Fahimzad et al, 2021 ; Pourakbari et al, 2021 ). Interestingly, neurological symptoms such as seizure, fatigue, and headache were also described ( Cheraghali et al, 2021 ; Fahimzad et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the most common symptoms reported in children, i.e., <18 years old, are cough and dyspnea ( Rabizadeh et al, 2020 ; Fahimzad et al, 2021 ) and fever and cough ( Hosseninasab et al, 2020 ; Mahmoudi et al, 2020 ; Armin et al, 2021 ; Hoseinyazdi et al, 2021 ; Mamishi et al, 2021 ; Soleimani et al, 2021 ; Keshavarz Valian et al, 2022 ). Gastrointestinal symptoms including vomiting, nausea, and diarrhea were reported but to a lesser extent ( Hosseninasab et al, 2020 ; Mamishi et al, 2020 ; Armin et al, 2021 ; Fahimzad et al, 2021 ; Pourakbari et al, 2021 ). Interestingly, neurological symptoms such as seizure, fatigue, and headache were also described ( Cheraghali et al, 2021 ; Fahimzad et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
“…Gastrointestinal symptoms including vomiting, nausea, and diarrhea were reported but to a lesser extent ( Hosseninasab et al, 2020 ; Mamishi et al, 2020 ; Armin et al, 2021 ; Fahimzad et al, 2021 ; Pourakbari et al, 2021 ). Interestingly, neurological symptoms such as seizure, fatigue, and headache were also described ( Cheraghali et al, 2021 ; Fahimzad et al, 2021 ). In one study, it was found that among hospitalized children with acute respiratory infection, those with COVID-19 had a higher frequency of respiratory distress and fever compared to those without ( Hosseninasab et al, 2020 ).…”
Section: Childrenmentioning
confidence: 99%
See 3 more Smart Citations